Characterization and mechanical properties of geopolymer materials using kaolin and white clay for coating application
Geopolymer exhibit a wide variety of properties in various applications including coating. Geopolymer as inorganic coating has good bonding structure of amorphous inorganic polymer which has excellent bonding agent properties and form at low temperature compare to organic coating. The use of new source materials such as kaolin and white clay has potential as geopolymer coating plus can reduce the use of existing cement as main material in existing cementitious coating. The performance of kaolin and white clay geopolymer coating has been tested on glass reinforced epoxy (GRE) pipe sample which provided from Saudi Arabia. The parameter to find the best mix design for kaolin and white clay is by fixing the solid/liquid ratio at 1.0 while the ratio of Na2SiO3/NaOH ratio is verified and has been cured at room temperature, 80°C, 200°C and 400°C to get the stable coating surface based on coating properties appearance before proceed to the strength testing. The microstructure of kaolin and white clay geopolymer coating were testing under chemical composition analysis, phase analysis and morphology analysis for raw materials (kaolin and white clay) and geopolymer coating products (kaolin and white clay). After sample of Na2SiO3/NaOH ratio from 0.40 – 0.60 can stand cured at room temperature, 80°C, 200°C and 400°C, sample then is proceed to mechanical strength testing by flexural strength, adhesive strength, water absorption, and hardness to get the best formulation. The morphology of the interfacial layer contact between substrate (glass reinforced epoxy sample) and geopolymer coating (kaolin and white clay) layer is studied using optical microscope. The best mix design for kaolin geopolymer coating was at 0.45 ratio Na2SiO3/NaOH with maximum flexural strength at 33.88 MPa. The adhesive strength at this mix design was among the highest strength which is 5.5 MPa as well as the water absorption achieved the lowest percentage at this mix design which is 1.91 %. During hardness test, the highest strength (229.8 MPa) was identified in the best mix design kaolin geopolymer coating.